Application of Scoring Methods in Web-Based Information Systems to Optimize Incentive Allocation for Honorary Teachers - Muhammad Fazel Ar Razia; Andi Nur Rachman; Genta Nazwar Tarempa (Journal of Applied Information System and Informatic (JAISI), 2026)
The distribution of incentive funds to honorary teachers in Indonesia is generally still carried out evenly without considering the differences in the real conditions of each recipient, resulting in proportional injustice. This study aims to design a prototype of a web-based Management Information System that applies a proportional scoring algorithm to optimize the allocation of incentive funds for honorary teachers. The methodology used is a prototyping approach with dummy data simulations, without field observations at specific institutions. The system is designed using native JavaScript and modelled with Unified Modelling Language (UML). The scoring algorithm weights four main variables: base points, income level, school geographic conditions, and educational level taught. Funds are then distributed proportionally based on each teacher's total points with a maximum limit equivalent to the City Minimum Wage (UMK). The system separates access between teachers and administrators, is equipped with a multilevel approval workflow, timeline-based status tracking, a statistical dashboard, allocation simulations, and reporting in PDF format. The design results show that the proportional scoring algorithm is able to produce a fairer and more transparent distribution than the flat method. Testing the algorithm's logic using simulated data resulted in 100% calculation consistency according to the defined rules. The implications of this research are expected to serve as a framework of reference for philanthropic institutions or zakat managers who wish to digitize the process of data collection and distribution of incentive funds to honorary educators in a more objective, accountable, and equitable manner.